2020
DOI: 10.2147/ijn.s263001
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Cerium Oxide on Lung Tissue in Lower Extremity Ischemia Reperfusion Injury in Sevoflurane Administered Rats</p>

Abstract: Introduction: We aimed to investigate the effects of cerium oxide, applied before the sevoflurane anesthesia, on lung tissue in rats with lower extremity ischemia-reperfusion (IR). Materials and Methods: A total of 30 rats were randomly divided into five groups as; control (C), IR, cerium oxide-IR (CO-IR), IR-sevoflurane (IRS), and cerium oxide-IRsevoflurane (CO-IRS). In the CO-IR group, 30 minutes after the injection of cerium oxide (0.5 mg/kg, intraperitoneal (i.p)), an atraumatic microvascular clamp was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The application of drugs in this way may also be considered as preconditioning. It has been proposed that antioxidant substances show their effects by preventing the increase in pulmonary microvascular permeability, neutrophil adhesion and accumulation or by binding to free oxygen radicals, thus showing their protective effects against distant organ injury that develop after I/R [ 10 , 11 , 27 , 28 , 29 ] In our study, positive results could only be achieved by propofol, and remifentanil showed no preventive effects on the injury.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The application of drugs in this way may also be considered as preconditioning. It has been proposed that antioxidant substances show their effects by preventing the increase in pulmonary microvascular permeability, neutrophil adhesion and accumulation or by binding to free oxygen radicals, thus showing their protective effects against distant organ injury that develop after I/R [ 10 , 11 , 27 , 28 , 29 ] In our study, positive results could only be achieved by propofol, and remifentanil showed no preventive effects on the injury.…”
Section: Discussionmentioning
confidence: 50%
“…Various studies have shown the protective effects of antioxidant compounds against distant organ injury developing after acute I/R injury. Although there have been a large number of drugs or substances that have been studied for their antioxidant effects and are being used for that purpose, anesthetic substances have a different and important place among them [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. One of these anesthetic substances that have been greatly emphasized is propofol.…”
Section: Introductionmentioning
confidence: 99%
“…Cerium oxide was given (0.5 mg/kg, ip) 30 minutes before the incision. Cerium oxide was given at the predetermined dose [ 16 ] Torsion-detorsion group (T/D): testis torsion/detorsion was performed surgically as described Cerium oxide-torsion-detorsion group (CeO 2 -T/D): testis torsion/detorsion was performed surgically as described. Cerium oxide was given (0.5 mg/kg , ip) 30 minutes before the ischemia period …”
Section: Methodsmentioning
confidence: 99%
“…Group IRI: midline laparotomy was performed, followed by 120 minutes of ischemia by clamping the infrarenal abdominal aorta by placing an atraumatic microvascular clamp, and then 120 minutes of reperfusion. 7 Group IRICO: 0.5mg/kg IP cerium oxide (Sigma-Aldrich, Co. St. Louis, MO, USA) was administered. Midline laparotomy was performed 30 minutes following the administration of CO, followed by 120 minutes ischemia and 120 minutes of reperfusion.…”
Section: Brief Communicationmentioning
confidence: 99%
“…[4][5][6] In our previous study, the combined effects of sevoflurane and CO on lung injury were investigated and it was revealed that they showed a stronger lung protective effect than their individual effects. 7 In this study, we aimed to study the combined effects of desflurane and CO on lung tissue following lower extremity IRI in rats.…”
mentioning
confidence: 99%